Impact of continuing professional development (CPD) activities on the career advancement of CPAs engaged in public practice in Makati - Afalla, Paola Therese M.; Amoto, Cyril Thomas L.; Honorio, Alyssa Angeli S.; Lodana, Maria Kyla B.; Lorenzo, Trisha Jaie E.; Manal, Joshua Reinand P.; Piangco, Marcedric George C. 4 0 16; 5
ABSTRACT: As a Certified Public Accountant (CPA) working in a fast-paced environment, having relevant skills, knowledge, and abilities are needed to be more efficient and proficient in the workplace they are in. Continuing Professional Development (CPD) is not only a way to ensure competency throughout a CPA's professional career, but it also facilitates knowledge creation and generation to the professionals availing it. However, for some CPAs, this primary objective of CPD is not highlighted; instead, they only view the CPD units they earn in such activities as a mere requirement for the renewal of their license. This study aims to challenge such a notion by knowing the level of impact perceived by the CPAs in Makati under the public practice of CPD activities. Specifically, this study wants to see the level of impact of such activities on the career advancement of the professional, which was further categorized into four areas, namely, their career development, financial income generation, development of professional networks, and improvement of their personal competencies. Furthermore, it also aims to identity if such levels of impact will be significantly different from each other when analyzed according to the respondents' demographic profiles. In the conduct of this study, the researchers used a descriptive-quantitative research design and administered the survey questionnaire through online means, and were able to gather responses from 151 CPAs under public practice in the City of Makati. The researchers were able to derive information from the data through the use of percentage, mean, standard deviation (SD), Kruskal-Wallis test, and Mann-Whitney test that the CPD activities have a significant impact on the career advancement of the CPAs, and such impact is not significantly different from each other when analyzed according to demographic profile. Even with the significant impact derived, the area regarding financial income was perceived as the least impactful to the CPAs. Thus, it was recommended by the researchers for CPD Providers to align their activities in improving and tackling the financial income aspect of the CPAs. Moreover, regulatory bodies can use the results of this study to evaluate their existing policies for their continuous improvement and effective implementation. Keywords: CPD Activities, CPAs in Makati, Career Advancement
Research Paper: (Bachelor of Science in Accountancy) - Pamantasan ng Lungsod ng Maynila, 2022
Keywords: 2 -- 0; 6; 20; 20; 2